2015
DOI: 10.1016/j.isprsjprs.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Mapping slope movements in Alpine environments using TerraSAR-X interferometric methods

Abstract: Mapping slope movements in Alpine environments is an increasingly important task in the context of climate change and natural hazard management. We propose the detection, mapping and inventorying of slope movements using different interferometric methods based on TerraSAR-X satellite images. Differential SAR interferograms (DInSAR), Persistent Scatterer Interferometry (PSI), Short-Baseline Interferometry (SBAS) and a semi-automated texture image analysis are presented and compared in order to determine their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 39 publications
2
59
0
3
Order By: Relevance
“…The mean of the absolute difference of time series displacements was 3.0 mm. The accuracy almost corresponded with previous PSI studies using TerraSAR-X, which shows that the PSI result agrees with the GPS data (e.g., Yu et al 2013;Luo et al 2014;Barboux et al 2015). The PSI result demonstrates that the local uplift area did not have a clear ellipsoidal shape, but rather had a more complex spatial pattern, such as a fractal surface, than that inferred by GPS analysis.…”
Section: Surface Displacement Derived From Psi Analysissupporting
confidence: 86%
“…The mean of the absolute difference of time series displacements was 3.0 mm. The accuracy almost corresponded with previous PSI studies using TerraSAR-X, which shows that the PSI result agrees with the GPS data (e.g., Yu et al 2013;Luo et al 2014;Barboux et al 2015). The PSI result demonstrates that the local uplift area did not have a clear ellipsoidal shape, but rather had a more complex spatial pattern, such as a fractal surface, than that inferred by GPS analysis.…”
Section: Surface Displacement Derived From Psi Analysissupporting
confidence: 86%
“…Nevertheless, displacements occurring parallel to the satellite track were largely underestimated. In this latter case, the PS-MTI technique might also have problems in the precise detection of points moving with velocities below 3.5 cm/year in the LOS, as found by Barboux et al [51].…”
Section: Discussionmentioning
confidence: 87%
“…Notti et al [50] demonstrated the potential of X-band SAR data using TerraSAR-X for landslide mapping and monitoring but a few natural PS were found in mountainous areas. Barboux et al [51] used the same band, combining PS-MTI and SBAS techniques for mapping slow movements in the Alps comparing these results to Real Time Kinematic GPS surveys. Barboux et al [52] was also limited to precisely detect points moving with velocities below 3.5 cm/year in the LOS by PS-MTI technique.…”
Section: Introductionmentioning
confidence: 99%
“…The most promising time series analyses for surface deformation in mountainous regions are PSI/IPTA (Persistent Scatterer Interferometry/Interferometric Point Target Analysis) and multidimensional SBAS (MSBAS) [29] [30]. Both techniques are using differential InSAR (DInSAR) using phase changes between two images in a given time to monitor lateral deformation, by filtering the topographic phase using a reference DEM.…”
Section: Geodetic Fixed Point Surveying Time Seriesmentioning
confidence: 99%